SEX EXPRESSION, BREEDING SYSTEM AND POLLINATORS OF Piper caldense (PIPERACEAE) IN THE BRAZILIAN ATLANTIC FOREST (2017)
Neotropical Piper species have bisexual flowers. Such reproductive trait is considered basal in this pantropical genus. However, neotropical species having unisexual (staminate) flowers along with bisexual ones have also been reported. Dichogamy is common in the genus, associated with either self-compatibility or -incompatibility, as well as with entomophily. We analyzed a natural population of Piper caldense in a Atlantic Forest area (Viçosa municipality, Minas Gerais state, southeastern Brazil). Preliminary observations indicated that the species produces two flower types. We analyzed flower sex in spikes of 50 plants. We obtained additional information through morphological and anatomical studies and scanning electron microscopy analyses. The longevity and exposure dynamics of stigmatic papillae and the pollen release sequence of all four stamens were investigated to verify the degree of dichogamy. Pollination tests were performed, pollinators were identified and their visitation frequency was recorded. Piper caldense has both bisexual and staminate flowers, each flower type being located on separate spikes. These spikes occurred on the same plant, thus indicating andromonoecy; furthermore, plants having only spikes with staminate flowers were also observed. This gender had not yet been reported to the genus. Gradual and sequential exposure of stigmatic papillae associated with asynchronous pollen release (one stamen a day) resulted in incomplete protogyny. Hand pollination tests showed that the species is self-incompatible. Social bees, mainly Apis mellifera and Melipona spp., were the major pollinator group. Our study reinforces the need to associate morphological analysis with floral biology and indicates future changes in studies addressing reproductive traits associated with the phylogeny of the Piper genus.